Perlindungan Hukum Terhadap Anak Sebagai Korban Tindak Pidana Kekerasan Seksual - Haerullah, Muhammad Fiqri; Marpaung, Devi Siti Hamzah (Peneliti.net, 2023)
Violence against children always increases every year, as a result, many victims of child violence experience deep trauma. Even though the government has issued the Child Protection Law Number 35 of 2014 on Amendments to the 2002 Child Protection Law regarding punishment for perpetrators of acts of violence against children, the facts are still not enough to address the problem of perpetrators of acts of violence against children. Legal protection for children as victims of sexual crimes in an abstract form is regulated in the Criminal Code which can be used to ensnare perpetrators of crimes against children, both sexual abuse and rape, as regulated in CHAPTER XIV. In addition, the perpetrators of crimes of sexual violence against children are also regulated by the government in Article 81 of Law no. 23 of 2002.